Phase advance of circadian rhythms in Smith–Magenis syndrome: A case study in an adult man. (12th January 2015) - Kocher, Laurence; Brun, Jocelyne; Devillard, Françoise; Azabou, Eric; Claustrat, Bruno
Highlights: An adult with Smith–Magenis syndrome displayed a phenotype of phase-advance. Sleep–wake cycle was phase-advanced. The plasma melatonin profile was reversed. Core body temperature displayed a phased-advance acrophase. The plasma cortisol profile showed a phased-advance acrophase. Abstract: Melatonin secretion is usually increased during the daytime and decreased at night in Smith–Magenis syndrome (SMS) and consequently is not a pertinent marker of the circadian phase of the clock in these cases. No data on temperature rhythm is available in SMS, another reliable marker of circadian clock activity. For this reason, we assessed the 24 h profiles of core temperature, sleep–wake cycle, hormones (plasma cortisol and melatonin) and plasma and urine 6sulfatoxy-melatonin, the main hepatic melatonin metabolism in a 31-year-old man diagnosed with a SMS. All circadian rhythms, especially temperature rhythm showed a phase-advance, associated with reverse melatonin secretion. Plasma and urine 6sulfatoxy-melatonin profiles showed normal melatonin catabolism and confirmed the reversed melatonin secretion. Taking in consideration the reverse melatonin secretion and the phase-advanced temperature rhythm, which is driven by the suprachiasmatic nucleus, we hypothesize that the central clock is more sensitive to afternoon than to morning melatonin. This different responsiveness to melatonin according to the time of the day (i.e. chronaesthesia) corroborates the phase response curve of melatonin secretion to exogenous melatonin.